2023
DOI: 10.3390/ani13172703
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Soil Temperature under Plateau Zokor’s (Eospalax baileyi) Disturbance in the Qinghai Lake Watershed, Northeast Qinghai–Tibet Plateau

Ting Xie,
Yu-Jun Ma

Abstract: The soil temperature is a key factor affecting the fragile terrestrial ecosystems on the Qinghai–Tibet Plateau, and has been remarkably altered by the soil mammal’s disturbance. This study first analyzed the soil temperature variation in grassland, mound, and bald patch under the disturbance of plateau zokor (Eospalax baileyi) from October 2018 to July 2020 in the Qinghai Lake watershed. Then, the SHAW (simultaneous heat and water) model was used to simulate the soil temperature change of three land surface ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Ye 21 et al showed that plant species richness increased signi cantly with the molehills' disturbance, which is in line with this paper's ndings. This is because with the succession of molehills, the number and species of aboveground vegetation on the molehills increased 22 , the species richness of grasses and perennial weeds increased, and the community composition and the degree of co-occurrence of species in the communities increased over time 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Ye 21 et al showed that plant species richness increased signi cantly with the molehills' disturbance, which is in line with this paper's ndings. This is because with the succession of molehills, the number and species of aboveground vegetation on the molehills increased 22 , the species richness of grasses and perennial weeds increased, and the community composition and the degree of co-occurrence of species in the communities increased over time 23 .…”
Section: Discussionmentioning
confidence: 99%